Pharmacological Inhibition of S-Nitrosoglutathione Reductase Reduces Cardiac Damage Induced by Ischemia–Reperfusion - Oscar Arriagada Castillo; Gustavo Herrera; Carlos Manriquez; Andrea F. Rojas; Daniel R. González (Antioxidants, 2021)
The cardioprotective effects of nitric oxide (NO) have been described through S-nitrosylation of several important proteins in the mitochondria of the cardiomyocyte. S-nitrosoglutathione reductase (GSNOR) is an enzyme involved in the metabolism of S-nitrosothiols by producing denitrosylation, thus limiting the cardioprotective effect of NO. The effect of GSNOR inhibition on the damage by cardiac ischemia–reperfusion is still unclear. We tested the hypothesis that pharmacological inhibition of GSNOR promotes cardioprotection by increasing the levels of protein S-nitrosylation. In a model of ischemia–reperfusion in isolated rat heart, the effect of a GSNOR inhibitor, 5-chloro-3-(2-[4-ethoxyphenyl) (ethyl) amino]-2-oxoethyl)-1H-indole-2-carboxylic acid (C2), was investigated. Ventricular function and hemodynamics were determined, in addition to tissue damage and S-nitrosylation of mitochondrial proteins. Hearts treated with C2 showed a lower release of myocardial damage marker creatine kinase and a reduction in the infarcted area. It also improved post-ischemia ventricular function compared to controls. These results were associated with increasing protein S-nitrosylation, specifically of the mitochondrial complexes III and V. The pharmacological inhibition of GSNOR showed a concentration-dependent cardioprotective effect, being observed in functional parameters and myocardial damage, which was maximal at 1 µmol/L, associated with increased S-nitrosylation of mitochondrial proteins. These data suggest that GSNOR is an interesting pharmacological target for cardiac reperfusion injury.